2000
DOI: 10.1677/jme.0.0250043
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression profiles for corticotrophin-releasing factor (CRF), urocortin, CRF receptors and CRF-binding protein in peripheral rat tissues

Abstract: The expression and activities of corticotrophinreleasing factor (CRF), urocortin (UCN), the CRF-binding protein (CRF-BP) and CRF receptors in rat brain have been well documented; however, information regarding their peripheral distributions remains incomplete. Given the multiple immunomodulatory effects of peripherally administered CRF and UCN and the high levels of CRF receptor type 2 (CRF-R2) mRNA and protein expressed in the heart, the lymphoid organs and heart have become targets for some of the latest CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 40 publications
1
63
1
7
Order By: Relevance
“…We found CRF, CRFBP, and CRF-R transcripts in multiple organs as has also been reported in mammals, amphibians and teleosts (De Souza et al, 1991;Baigent and Lowry, 2000;Muramatsu et al, 2000;Kimura et al, 2002;Boorse and Denver, 2004;Huising et al, 2007). Since urocortin, a CRF-related peptide, can interact with CRF-R2 to protect the heart from ischemia in rats and humans (Baigent and Lowry, 2000;Kimura et al, 2002), it is particularly interesting that we also found CRF, CRFBP and CRF-R2 mRNA expressed in skeletal muscle and cardiac muscle in the teleost.…”
Section: Crf Systems Are Expressed In the Peripheral Tissuessupporting
confidence: 85%
See 2 more Smart Citations
“…We found CRF, CRFBP, and CRF-R transcripts in multiple organs as has also been reported in mammals, amphibians and teleosts (De Souza et al, 1991;Baigent and Lowry, 2000;Muramatsu et al, 2000;Kimura et al, 2002;Boorse and Denver, 2004;Huising et al, 2007). Since urocortin, a CRF-related peptide, can interact with CRF-R2 to protect the heart from ischemia in rats and humans (Baigent and Lowry, 2000;Kimura et al, 2002), it is particularly interesting that we also found CRF, CRFBP and CRF-R2 mRNA expressed in skeletal muscle and cardiac muscle in the teleost.…”
Section: Crf Systems Are Expressed In the Peripheral Tissuessupporting
confidence: 85%
“…Since urocortin, a CRF-related peptide, can interact with CRF-R2 to protect the heart from ischemia in rats and humans (Baigent and Lowry, 2000;Kimura et al, 2002), it is particularly interesting that we also found CRF, CRFBP and CRF-R2 mRNA expressed in skeletal muscle and cardiac muscle in the teleost. This suggests that the cardiac CRF system may mediate the adaptive response of the heart to stress in all vertebrates, from teleosts to mammals (Coste et al, 2002).…”
Section: Crf Systems Are Expressed In the Peripheral Tissuesmentioning
confidence: 73%
See 1 more Smart Citation
“…Corticotropin-releasing factor (CRF) is a 41 amino acid neuropeptide that in mammals controls a wide range of physiological responses to physical and emotional stressors (e.g., Tsigos and Chrousos, 2002;Vale et al, 1981), including neuroendocrine and behavioral responses, inXammatory responses to immunological agents, and modulation of gastrointestinal (Baigent and Lowry, 2000) and cardiovascular activity (Parkes et al, 2001). Urocortin 1 (Ucn1) is a 40 amino acid peptide structurally related to CRF.…”
Section: Introductionmentioning
confidence: 99%
“…I t is now well-established that corticotropin-releasing factor (CRF) 4 and its related peptides affect the inflammatory response in a paracrine/autocrine manner (1)(2)(3)(4)(5)(6)(7)(8). CRF acts as an ad hoc proinflammatory factor because blockade of its effect by specific anti-CRF serum or CRF antagonists attenuates the inflammatory response in several models of inflammation including that of carrageenin, turpentine, and Gram-negative bacterial LPS-induced inflammation (9 -11).…”
mentioning
confidence: 99%